2020
DOI: 10.1111/nhs.12693
|View full text |Cite
|
Sign up to set email alerts
|

Graduated nurses' experiences with baccalaureate thesis writing: A qualitative study

Abstract: This study explores the perceptions of newly graduated nurses regarding the baccalaureate thesis (BT) writing process. A qualitative approach with content analysis was adopted. Thirteen newly graduated nurses participated in the study. The inclusion criterion was having completed the BT during their university education as nurses within 3 years of the study. Information was obtained through semistructured interviews. Data collection began in June 2018 and ended in March 2019, once saturation of information was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(36 reference statements)
0
2
0
1
Order By: Relevance
“…Furthermore, in Henttonen et al [38] about expectations when writing a thesis, the nursing students hoped to obtain valuable knowledge for professional practice. In our study, they attained this knowledge, reflected by their high satisfaction rate, although the writing process generated anxiety and difficulty due to a specific lack of training [39].…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, in Henttonen et al [38] about expectations when writing a thesis, the nursing students hoped to obtain valuable knowledge for professional practice. In our study, they attained this knowledge, reflected by their high satisfaction rate, although the writing process generated anxiety and difficulty due to a specific lack of training [39].…”
Section: Discussionmentioning
confidence: 60%
“…En consecuencia, las investigaciones empíricas que apoyan el desarrollo de este género podrían ser un apoyo importante para los tesistas. El segundo lugar de ocurrencia (barras verdes del Gráfico 5) es para aquellas investigaciones cuyo objeto de análisis corresponde a la transcripción de entrevistas realizadas en torno al género Tesis o a su proceso de escritura (17,46 %) (Marinkovich y Salazar, 2011;Tapia-Ladino y Marinkovich, 2011;Colombo, 2014;Aguayo-González et al, 2020; entre otros casos). Este resultado evidencia que la preocupación por la Tesis no solo ha estado en el producto textual mismo, sino también en abordajes menos lingüísticos y más sociales del género en cuestión.…”
Section: Gráfico 4 Grado Académico En Los Que Se Enfocan Los Artículo...unclassified
“…Previous studies have shown that nursing students feel their first years of education do not prepare them for developing scientific academic texts or for reflective writing with a sufficient level of academic rigor, 8 but mainly for a synthetic type of writing required in clinical scenarios. 9 Several models have been proposed for supporting students and providing them with the skills needed to write their degree projects. Dysthe 10 divided the existing supervising and mentoring scenarios into three different models: the teaching model, the partnership model and the apprenticeship model.…”
Section: Introductionmentioning
confidence: 99%